Literacy Development of Roma Children in L2: A Comparative Psycholinguistic Study - Kyuchukov, Hristo (East European Journal of Psycholinguistics, 2021)
The paper presents results from a comparative empirical L1 / L2 literacy study with first-grade Roma and non-Roma children, resident in Bulgaria and Slovakia. The Roma children growing up in traditional communities are socialized through the rich oral culture surrounding them. In the extended Roma families, the care of the children is responsibility of everyone. In such a rich speech environment, the children learn their mother tongue. However, the oral skills of Roma children acquired in the home environment are not used at all in the process of literacy development in their L2 at primary school, neither in Bulgaria nor in Slovakia. Bialystok (2007) says that the oral skills of bilingual children in their L1 and L2 play an important role in the preparation for literacy. The Roma children’s oral skills in their L1 are not further developed at the primary school level and their L2 oral skills are initially often very limited. 60 first-grade children (20 Roma and 40 non-Roma children) were tested using the RAN Test at the end of the school year, in Bulgarian and Slovak. Various aspects, including comparative differences in literacy performance between Roma children tested in Bulgaria and Slovakia, are discussed in detail. The findings show that (1) the time for naming the RAN Test in L2 can be used as a predictor for the children’s literacy level in L2; (2) A low level of language competence of the children in their L1 appears congruent with a low literacy proficiency in L2; (3) The place of residence of the children appears to be a factor influencing the performance by Roma children in the RAN Test. The Roma children from the village have better results than Roma children living in the city. The level of oral proficiency in L1 of Roma children influences the timing of the naming of the RAN Test in L2. The Roma children resident in town have a more isolated life and do not possess such a rich vocabulary in their mother tongue. The children living in a village have more daily contact with non-Roma Bulgarians, for example, and thus develop a richer vocabulary in their mother tongue as well.